Nuclear Spectral Energy Distributions of Luminous Infrared Galaxies - Tianmu Gao; Vivian U; Connor W. Auge; Yiqing Song; Sean T. Linden; Kazushi Iwasawa; Alessandro Peca; George C. Privon; David B. Sanders; Núria Torres-Albà; Loreto Barcos-Muñoz; James Agostino; et al. (The Astrophysical Journal, 2025)
We present nuclear (100–150 pc) spectral energy distributions (SEDs) for a sample of 23 nearby luminous infrared galaxies hosting a total of 28 nuclei. We gather aperture photometry from high-resolution X-ray to submillimeter data for each nuclear region localized by Atacama Large Millimeter/submillimeter Array observations of the dust continuum. We model the broadband SEDs using X-CIGALE. Binning the merging systems by interaction class, we find that the active galactic nucleus (AGN) fraction (fraction of AGN infrared luminosity to total infrared luminosity) appears enhanced in the late- and post-merger stages compared to the early-merger stage. Examining the relationship between X-ray emission and infrared emission of the nuclear regions, we find that the infrared emission in the nuclei is dominated by dust and AGNs, with minimal contribution from stars. We also find that nuclear regions have higher X-ray hardness ratios than the host galaxies globally among both the AGN and non-AGN population. We highlight the similarities and differences in the SEDs of dual nuclei in five closely separated late-stage merging systems: Arp 220 ( d _nuc  ∼ 0.5 kpc), NGC 6240 ( d _nuc  ∼ 1 kpc), IRAS 07251−0248 ( d _nuc  ∼ 2 kpc), IRAS F12112+0305 ( d _nuc  ∼ 4 kpc), and IRAS F14348+1447 ( d _nuc  ∼ 6 kpc). The SEDs for these resolved pairs are distinct, suggesting that the AGN state is much more susceptible to the stellar and dust content within the immediate circumnuclear (<150 pc) environment than to the host’s global infrared luminosity or merger stage.